Yleisesitys Itä-Saksan historiasta - Wilska, Juho (Turun yliopisto/Poliittinen historia, 2025)
Kirja-arvostelu teoksesta:
Katja Hoyer: Muurin takana. Itä-Saksan historia 1949–1990. [Beyond the Wall.] Suom. Mari Janatuinen. Atena, 2023. 550 s.